Studies on some new pyrazolo[3,4-c]pyridine derivatives as antimicrobial agents [Antimikrobiyal ajan olarak bazi yeni pirazolo[3,4-c]piridin türevleri üzerine çahsmalar] - (:unkn) unknown (My University, 2009)
The increasing clinical importance of drug-resistant bacterial and fungal pathogens has lent additional urgency to microbiological research and novel antimicrobial compounds development. For this aim, a series of N-[(Benzhydryl) / (l-phenylethyl)]-2-pyrazolo[3,4-c]pyridin-l-yl acetamide derivatives (3a-m) were synthesized by reacting 2-chloro-N-(benzhydryl)acetamide (la) / 2-chloro-N-(1-phenylethyl)acetamide (lb) and pyrazolo[3,4-c]pyridine derivatives (2). The chemical structures of the compounds were elucidated by elemental analyses, IR, 1H-NMR, FAB+-MS spectral data. Their antimicrobial activities against E. coli (ATCC 11229), S. aureus (ATCC 6538), B. cereus (ATCC 11778), P. mirabilis (ATCC 14153), P. aeruginosa (ATCC 1539), K. pneumoniae (ATCC 4352), C albicans (ATCC 26555), C guilliermondii (KUEN 998), C pseudotropicalis (kefyr) (KUEN 1014), and C krusei (ATCC 6258) were investigated. The results showed that some of the compounds have slight activity against B. cereus and S. aureus. Whereas, the same compounds did not show any significant antifungal activity against Candida species.
Keywords: Acetamide; Antimicrobial activity; Pyrazolo[3,4-c]pyridine derivatives